2006
DOI: 10.1088/0031-9155/51/10/001
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach for inversion problems in intensity-modulated radiation therapy

Abstract: We propose and study a unified model for handling dose constraints (physical dose, equivalent uniform dose (EUD), etc) and radiation source constraints in a single mathematical framework based on the split feasibility problem. The model does not impose on the constraints an exogenous objective (merit) function. The optimization algorithm minimizes a weighted proximity function that measures the sum of the squares of the distances to the constraint sets. This guarantees convergence to a feasible solution point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
373
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 745 publications
(414 citation statements)
references
References 31 publications
1
373
0
1
Order By: Relevance
“…Many problems in mathematics and other sciences can be regarded as a split equality problem, such as the variational form of a PDE's in domain decomposition for PDE's [3], the agents who interplay only via some components of their decision variables in decision [2] and the weak coupling between the vector of doses absorbed in all voxels and that of the radiation intensity in the (IMRT) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many problems in mathematics and other sciences can be regarded as a split equality problem, such as the variational form of a PDE's in domain decomposition for PDE's [3], the agents who interplay only via some components of their decision variables in decision [2] and the weak coupling between the vector of doses absorbed in all voxels and that of the radiation intensity in the (IMRT) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the split feasibility problem can also be used in various disciplines such as image restoration, computer tomograph and radiation therapy treatment planning [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the SFP has received so much attention due to its applications in intensity-modulated radiation therapy, signal processing, and image reconstruction, see Byrne [1,2], Censor [4][5][6], Ceng [3], Fan et al [7], Xu [20,21], Kraikaew and Saejung [9], Moudafi [10], Qu et al [12][13][14], Qin and Yao [11], Yang et al [16,22,27,28], Yao et al [23][24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%